新形蜗杆砂轮无轴向进给磨削圆柱齿轮技术原理 - 张学成; 于立娟; 李春光 (Jixie chuandong)
According to the analysis on the principle of spatial skew axis helical gearing with instantaneous straight line contact,a new type worm is established.It is a screw gearing in which the worm and wheel are in contact with a straight line.And the worm and wheel all are helical gear,but the worm is a special helical gear with one teeth and tremendous base helix angle,and the wheel is a helical gear with small base helix angle.Alternate angle of the axes of the wheels are close to right angle.When the length of the worm tooth surface generating line is more than the gear width,one side of the worm tooth surface would be contacted with the gear tooth surface all over the width in the process of transmission,and one feature is larger relative sliding velocity of the tooth surface.In the foundation,a new grinding gears technique with the new worm grinding wheel without axial feeding is proposed.The principle and method of the technique are discussed in detail,in which double worm grinding wheel would be used.And how to realize the structure of the machine and grinding feed, grinding velocity formula are given.There are non-axial feeding,larger relative sliding velocity of the tooth surface,simple structure,and higher efficient in this technology.It’s suitable for grinding gears and honing gears in large numbers.